2021
DOI: 10.3390/ijerph18189744
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Delivery and Acceptability of the ROWTATE Telehealth Vocational Rehabilitation Intervention for Traumatic Injury Survivors: A Mixed-Methods Study

Abstract: Background: Returning to work after traumatic injury can be problematic. We developed a vocational telerehabilitation (VR) intervention for trauma survivors, delivered by trained occupational therapists (OTs) and clinical psychologists (CPs), and explored factors affecting delivery and acceptability in a feasibility study. Methods: Surveys pre- (5 OTs, 2 CPs) and post-training (3 OTs, 1 CP); interviews pre- (5 OTs, 2 CPs) and post-intervention (4 trauma survivors, 4 OTs, 2 CPs). Mean survey scores for 14 theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Recently, more and more other studies discussed the implications of telemedicine in orthopedics from various aspects. [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more other studies discussed the implications of telemedicine in orthopedics from various aspects. [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Consistent with our findings, a study of a telehealth vocational rehabilitation intervention also found that remote delivery reduced the burden for patients as they felt more comfortable receiving therapy at home and did not need to travel to access the programme. 16 Reduced travel demands and childcare requirements also contribute to the acceptability of virtual consultations in an orthopaedic setting. 17 In contrast, other participants in our study reported that childcare responsibilities were a distraction which could reduce the programme’s effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Participants randomized to the experimental group will receive early vocational rehabilitation (the Work intervention) to address individualized goals set in relation to work and working in addition to usual clinical rehabilitation. The vocational intervention will be predominantly delivered face to face, but there is potential to deliver using telehealth [ 18 ]. Whether in-person or via telehealth, the intervention will be delivered on a one-to-one basis and be individually tailored to the participant in terms of content, dose, intensity, and duration according to participants’ needs and preferences (eg, whether the participant consents to employer liaison and workplace visits).…”
Section: Methodsmentioning
confidence: 99%